2014
DOI: 10.15414/jmbfs.2014.4.2.93-101
|View full text |Cite
|
Sign up to set email alerts
|

Product Safety and Color Characteristics of Ground Beef Processed From Beef Trimmings Treated With Peroxyacetic Acid Alone or Followed by Novel Organic Acids

Abstract: Keywords: non-STEC O157:H7, Salmonella spp., meat safety, instrumental color

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…While it can be confirmed that decontamination can be used to effectively reduce the number of microorganisms, it must be viewed as a meat safety strategy to be added to existing programs of hygiene, such as the use of a two-knifes system during animal slaughter and dressing, prevention of animal hide from coming into contact with already dressed sides and meat inspection/trimming to physically remove visible contamination already implemented during slaughter [22]. Reference [23] note that various processes of meat decontamination are not generally accepted across the globe. For example, the United States of America (USA) has effectively implemented a carcass decontamination plan, whilst some European countries do not fully endorse the use of decontaminates as a form of improving the safety of meat products, with an exception of lactic acid and potable (chlorinated) water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it can be confirmed that decontamination can be used to effectively reduce the number of microorganisms, it must be viewed as a meat safety strategy to be added to existing programs of hygiene, such as the use of a two-knifes system during animal slaughter and dressing, prevention of animal hide from coming into contact with already dressed sides and meat inspection/trimming to physically remove visible contamination already implemented during slaughter [22]. Reference [23] note that various processes of meat decontamination are not generally accepted across the globe. For example, the United States of America (USA) has effectively implemented a carcass decontamination plan, whilst some European countries do not fully endorse the use of decontaminates as a form of improving the safety of meat products, with an exception of lactic acid and potable (chlorinated) water.…”
Section: Introductionmentioning
confidence: 99%
“…However, the obligation lies with industry to prove the efficiency and effectiveness of a decontamination system before it can be approved to be used in the meat industry [24]. Given the ever-changing environments and the ever-growing demand for meat and thus demand for slaughter, measures that can benefit the industry and at the same time improve the safety of a specific product must be developed and implemented [23]. Many researchers have identified citric, lactic and acetic acid as possible organic acids that can be used to reduce some types and numbers of microorganisms in wild ungulate species meat.…”
Section: Introductionmentioning
confidence: 99%
“…Few developed and developing countries endorse the use of decontamination. For example, the United States of America (USA) allows for carcass decontamination plans, while some European countries do not fully approve the use of decontamination as a form of improving the safety of meat products with an exception for LA and chlorinated water [20,24]. In South Africa, no method of the decontamination of fresh red meat is allowed, except for the use of potable water for the rinsing of fresh carcasses after slaughter before chilling, except with the approval of a provincial executive officer of Veterinary Services [25].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore in the interest of South Africa and other receiving countries to obtain more scientific information that will inform the current reservations among policy makers and the game meat industry. While there are many OA used for carcass decontamination interventions, LA and AA have predominantly been adopted in meat products and carcasses in developed countries; mainly because of their availability in many regions of the world [6,24]. This paper, therefore, investigated the decontamination effect and efficiency of potable water typically used for washing carcasses in comparison to the use of LA and AA as decontaminants of wound areas caused during the killing of impala at a commercial game abattoir in South Africa.…”
Section: Introductionmentioning
confidence: 99%